Evolution of Emotions from the Movie Matilda 1996 to the Movie Matilda 2022 (Comparative Analysis Study) - Adinda Dwi Cahyani; Nahdhiyah Nahdhiyah; Muhammad Taufik; Citra Andini (Hasanuddin University, 2025)
This research aims to compare the emotions depicted in the main character in the 1996 movie Matilda to the movie Matilda in 2022. This research investigates the emotional evolution that occurs from the movie Matilda 1996 to the movie Matilda 2022. This research is comparative diachronic research by Zepetnek theory and uses a character psychology approach in literary works. In obtaining data, this research was analyzed using Elizabeth B. Hurlok's theory of children's emotions and applying qualitative descriptive methods with notetaking as a research instrument. The results of this research show that there are types of emotions children get from the character Matilda: emotions of anger, joy or happiness, grief, curiosity, fear and affection. Therefore, the researchers concluded that the emotions that occur in the character Matilda from the 1996 movie Matilda to the movie Matilda 2022 show that Matilda 2022 is more aggressive, more expressive, and braver than the movie Matilda 1996. Overall, this research reveals evolution of emotions that are influenced by the author's mindset towards children's characters related to current developments.